THE EFFECT OF TRANSFORMATIONAL LEADERSHIP ON TEACHER PERFORMANCE AND STUDENT ACHIEVEMENT: ANALYSIS OF SCHOOLS IN REMOTE AREAS - Sri Astuti; Onny Fitriana S (International Journal of Teaching and Learning, 2025)
This research aims to examine the influence of transformational leadership on teacher performance and student achievement in schools located in remote areas. Transformational leadership, characterized by a clear vision, inspirational motivation, intellectual stimulation, and individual attention, is believed to bring positive change in educational environments that are often faced with limited resources. The research method used is a literature study with qualitative analysis of various relevant academic journals, books and previous research reports. The results of the study show that transformational leadership has a significant influence on improving teacher performance through providing motivation, support and continuous professional development. Apart from that, transformational leadership also contributes positively to student achievement, both in academic and non-academic terms, by creating a conducive and inspiring learning environment. However, there are several challenges faced in implementing transformational leadership in remote areas, including limited access to training and resources. It is hoped that the findings of this research will provide insight for educational policy makers and school practitioners in designing effective leadership strategies to improve the quality of education in remote areas.